STUDI EKSEGESIS TENTANG CIPTAAN BARU DALAM 2 KORINTUS 5:17 DAN IMPLEMENTASINYA BAGI MAHASISWA SEKOLAH TINGGI TEOLOGI DUTA PANISAL JEMBER - Pebrianto Sitanggang (Alucio Dei, 2020)
As Christians or believers must remember that a new life in Christ is demanded to have a new way of life that is different from those who do not yet know Christ. Therefore, understanding the new creation in Christ through exegesis is very important to be carried out as a guideline for every person especially to every collage student at the Duta Panisal Theological Seminary in Jember. The purpose of writing this thesis journal is to find out what is meant by a new creation, what are the indicators and what are the implementations of the new creation contained in 2 Corinthians 5:17. The research method used in the writing of this thesis is a qualitative method. The results of writing this thesis are real that students need to apply the concept of new creation in the life of the boarding house